2022
DOI: 10.1590/0034-7167-2021-0594
|View full text |Cite
|
Sign up to set email alerts
|

Is social isolation during the COVID-19 pandemic a risk factor for depression?

Abstract: Objective: To assess factors associated with depression among higher education students and professionals during the peak of the COVID-19 pandemic. Method: quantitative study with a cross-sectional design. 550 students and professionals participated. The data were collected by means of a digital questionnaire that included Patient Health Questionnaire-9 to assess depressive symptoms. Results: The factors related to depression and social isolation outcomes were significantly associated with the female gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
0
8
0
8
Order By: Relevance
“…In relation to the positive strategies, a number of studies showed that preservation of social ties, even if virtual, made men less prone to presenting depression and anxiety symptoms, reinforcing the need for interventions aimed at promoting health literacy, connectivity, and social support for men to help minimize some psychosocial problems, such as impacts induced by COVID-19 ( Moreira et al, 2021 ; Moura et al, 2022 ; Nguyen et al, 2020 ; Paakkari & Okan, 2020 ; Sentell et al, 2020 ; Simpson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the positive strategies, a number of studies showed that preservation of social ties, even if virtual, made men less prone to presenting depression and anxiety symptoms, reinforcing the need for interventions aimed at promoting health literacy, connectivity, and social support for men to help minimize some psychosocial problems, such as impacts induced by COVID-19 ( Moreira et al, 2021 ; Moura et al, 2022 ; Nguyen et al, 2020 ; Paakkari & Okan, 2020 ; Sentell et al, 2020 ; Simpson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID losses are a public health issue and the psychological processing of this cannot be clumped in with other models. However, it is widely acknowledged that mental health is a public health issue, and research has extensively identified that the impact of lockdown was severe ( 6 , 7 ) and low mood identified as a real concern ( 8 ). The Afghanistani crisis that arose alongside the pandemic resulted in a secondary global public health concern and strategies to support these communities need to be considered ( 9 ).…”
Section: A Public Health Issuementioning
confidence: 99%
“…Increased use of alcoholic beverages during the pandemic was reported by 69% of health professionals in the present sample. In addition, research with doctors in Italy (Sio et al, 2020), with health workers in London (Papa et al, 2021), with workers in Finland (Oksanen et al, 2021), with university students J o u r n a l P r e -p r o o f (Moura et al, 2022) and population-based research in Germany (Koopmann et al, 2020) and Poland (Szajnoga et al, 2021), reported increased consumption of alcoholic beverages during the COVID-19 pandemic, showing that the trend of increasing consumption of alcoholic beverages occurs in the population as a whole. However, it is expected that public policies for control and regulation would reduce consumption as they reduce the areas where alcohol can be consumed, such as bars, restaurants, parties and celebrations.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Occupation and educational status are still factors that place women at a socioeconomic disadvantage and exacerbate the vulnerable situations of those abusing or dependent on psychoactive substances. Moreover, other factors related to social and economic issues can also explain the greater use of substances among more educated women, as observed in recent decades (Moura et al, 2022;Santos et al, 2019).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%